A terceirização irrestrita e suas implicações na educação básica pública brasileira - Pereira, Leoclécio Dobrovoski Silva (2023)
This study was developed in the Graduate Program in Education at the Faculty of Education at the Federal University of Uberlândia, in the research line Work, Society and Education. The objective is to understand the developments of New Public Management [Nova Gestão Pública] (1990) related to the work of teachers in Brazilian public Basic Education and their processes of insecurity. Under the argument of the State's budgetary incapacity to manage the public machine, emanated by the reformers, consensus building aimed at administrative efficiency from business management was established, justifying its adoption as a prototype in public services. In this sense, in addition to transferring the processes developed in the private sector to the public sector, it began to offer services previously exclusive to public agencies through privatizations, partnerships, and management contracts. In this context, we elected to analyze what we conventionally call Unrestricted Outsourcing [Terceirização Irrestrita] in public Basic Education, sanctioned by the government of Michel Temer in 2017 through Law 13.429/2017. As a rule, the law allows outsourcing of middle and end activities in a particular organization, and in terms of public Basic Education, it covers everything from maintenance and conservation services to management positions and even teaching positions, which is now the case in two schools in the city of Uberlândia-MG. The research was carried out based on Historical and Dialectical Materialism and was based on a literature review, document analysis and case study. As a result, we point out that the Unrestricted Outsourcing in the public service constitutes a process of “privatization from the inside”, insofar as the private initiative is inserted in the provision of public services to the population and funded by the public entity and, ultimately, by the public entity itself. contributing citizen. Regarding to teaching work under this scope, we identified the expansion of insecurity processes, embodied in withdrawal of rights, devaluation of work and wage reduction. The research was carried out anchored in Historical and Dialectical Materialism and was based on literature review and field research. As results, we point out that Unrestricted Outsourcing in the public service constitutes a process of “privatization from within”, in which the private sector is inserted into the provision of public services to the population and paid for by the public entity and, ultimately, by the taxpayer. Regarding teaching work under this scope, we identified the expansion of processes of insecurity, consisting of the withdrawal of rights, devaluation of work and salary reductions